Balanced Scorecard: Analisis Kinerja PT Bank Syariah Indonesia Tbk - Ma'rifatul Husniyah; Ade Ilham Ilahi; Lidiya Merti Putri; John Suprihanto (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2023)
Purpose: This study compares the performance of PT Bank Syariah Indonesia using the balanced scorecard approach in the period before and after the merger.Method: Qualitative method with research data from annual reports for the 2020-2021 period, namely the period before and after the merger of Bank Syariah Indonesia.Results: The results showed that from a financial perspective, after experiencing a merger, the combined ROE ratio of the three Islamic banks was getting better and included healthy qualifications because it was close to 15%. Customer perspective, the profitability obtained from customers increased quite well supported by customer growth due to migration from the predecessor bank to the merged bank and new customer growth. Growth and learning perspective, the merged company experienced operating efficiency due to the synergy of the merger and caused the calculation of employee productivity as measured by company revenue to increase. Internal business process perspective, The form of innovation is in the form of establishing several business unit networks that can facilitate services.Implications: This research provides a deeper look into performance measurement using data from the company's published annual reports.Novelty: This study focuses on the use of ratios from financial reports and company annual reports to measure each perspective in the balanced scorecard. Previous balanced scorecard studies used survey methods to obtain information related to growth and learning perspectives, as well as customer perspectives and internal business process perspectives, while this study uses data from only financial reports and company annual reports.